Stability of non-fullerene acceptor-based organic solar cells: chemical and physical properties at the interfaces and active layer - Ian C Flores; Yenny L Casallas-Moreno; Ángel Sacramento; Magali Ramírez-Como; Marlene Camacho-Reynoso; Víctor Cabrera; Yuriy Kudriavtsev; Carlos Rivera-Rodríguez; Luis M Reséndiz (Materials Research Express)
Organic solar cells (OSCs) have improved power conversion efficiency (PCE); however, their stability remains challenging. This study evaluates the chemical stability and performance of non-fullerene acceptor-based OSCs (NFA-OSCs) using a blend of Poly[(2,6-(4,8-bis(5-(2-ethylhexyl-3-fluoro)thiophen-2-yl)-benzo[1,2-b:4,5-b’]dithiophene))-alt-(5,5-(1’,3’-di-2-thienyl-5’,7’-bis(2-ethylhexyl)benzo[1’,2’-c:4’,5’-c’]dithiophene-4,8-dione)] (PM6) and 2,2’-((2Z,2’Z)-((12,13-bis(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2’,3’‘:4’,5’]thieno[2’,3’:4,5]pyrrolo[3,2-g]thieno[2’,3’:4,5]thieno[3,2-b]indole-2,10-diyl)bis(methanylylidene))bis(5,6-dichloro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile (Y7). Inverted organic solar cells (iOSCs) were examined using indium tin oxide (ITO) as the cathode, N,N’-Bis(N,N-dimethylpropan-1-amine oxide)perylene-3,4,9,10-tetracarboxylic diimide (PDINO) as the electron transport layer (ETL), PM6:Y7 as the active layer, molybdenum trioxide (MoO _3 ) as the hole transport layer (HTL), and silver (Ag) as the anode. Over 270 days, without voltage application, NFA-iOSCs were exposed to ambient conditions, room temperature (RT) of 19.4 ± 0.4 °C and a relative humidity (RH) of 50 ± 5%, and monitored using time-of-flight secondary ion mass spectroscopy (TOF-SIMS), x-ray photoelectron spectroscopy (XPS), ultraviolet–visible spectroscopy (UV–vis), and Raman spectroscopy. The results showed that the active layer maintained stability with minimal degradation with or without protective layers (Ag and MoO _3 ). The TOF-SIMS and XPS analyses confirmed that oxygen did not diffuse into the layers where it was initially absent, thereby ensuring chemical stability. Raman spectroscopy results supported these findings, showing stable vibrational modes over time. This study highlights the degradation mechanisms of NFA-OSCs and the importance of protective layers in extending the device lifetime, contributing to the durability and commercial viability of OSCs, and advancing sustainable solar energy technologies.